Answer:
![\large \boxed{\sf \ \ \ 4 \ \ \ }](https://img.qammunity.org/2021/formulas/mathematics/high-school/f0botkgisnsaovhf5i0yc8iw5o4ncezfnj.png)
Explanation:
Hello, please find below my work.
![x^2-4x-1=0 \ \ \text{add 1 to both parts of the equation}\\\\<=> x^2-4x-1+1=0+1=1\\\\<=> x^2-4x=1](https://img.qammunity.org/2021/formulas/mathematics/high-school/ub0r5gqhsy2jmaqw2qi2z3wxm6g0mk6iaf.png)
We know that for any a and x real numbers we can write
![(x-a)^2=x^2-2ax+a^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e0va4gbwnprdvz5l6464fy6r91h4oy6q4i.png)
When we compare with the left part of the equation we can identify the term in x so that -4=-2a (multiply by -1) <=>4=2a (divide by 2) <=> a = 4/2 = 2
So we can write
![(x-2)^2=x^2-4x+2^2=x^2-4x+4](https://img.qammunity.org/2021/formulas/mathematics/high-school/mze6l7xomkk5qk9xfdw7pvspvdiliikozr.png)
So we have to add 4 to both sides of the equation to complete the square and it comes:
![x^2-4x-1=0 \ \ \text{add 1 to both parts of the equation}\\\\<=> x^2-4x-1+1=0+1=1\\\\<=> x^2-4x=1 \ \boxed{\text{ add 4 to complete the square}} \\\\<=>x^2-4x\boxed{+4}=1+4=5\\\\<=>(x-2)^2=5 \ \text{ we take the root } \\ \\ <=>x-2=\pm √(5)\ \text{ we add 2 } \\ \\ <=> x = 2+√(5) \ \text{ or } \ x = 2-√(5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/sd1mrjfkew4udunafgd0pdon44phi22ek3.png)
Hope this helps.
Do not hesitate if you need further explanation.
Thank you